2017
DOI: 10.1007/s10103-016-2139-9
|View full text |Cite
|
Sign up to set email alerts
|

Does photobiomodulation therapy is better than cryotherapy in muscle recovery after a high-intensity exercise? A randomized, double-blind, placebo-controlled clinical trial

Abstract: This study aimed to determine the effectiveness of photobiomodulation therapy (PBMT) and cryotherapy, in isolated and combined forms, as muscle recovery techniques after muscle fatigue-inducing protocol. Forty volunteers were randomly divided into five groups: a placebo group (PG); a PBMT group (PBMT); a cryotherapy group (CG); a cryotherapy-PBMT group (CPG); and a PBMT-cryotherapy group (PCG). All subjects performed four sessions at 24-h intervals, during which they submitted to isometric assessment (MVC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 47 publications
0
37
1
5
Order By: Relevance
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout.…”
Section: Best Evidencementioning
confidence: 83%
See 4 more Smart Citations
“…[4][5][6][7][8] There were no studies found in the literature search that supported cryotherapy over PBMT. The PBMT was more effective in preventing increases in CK levels, 4-8 blood lactate, 5 C-reactive protein, 5,7 and inflammation 6,7 after an exercise bout.…”
Section: Best Evidencementioning
confidence: 83%
“…12,25 Muscle damage was noted in the included studies following the exercise protocols. This was demonstrated by an increase of CK, blood lactate, and frequency of necrosis, measured by histological analysis, in placebo treatments, 4,5,8 an ice bag application, 4,8 and coldwater immersion therapy. 5,7 Compared with placebo treated groups, cryotherapy demonstrated no difference in CK 4,5,8 or blood lactate 5 levels at any time points.…”
Section: Best Evidencementioning
confidence: 99%
See 3 more Smart Citations